Reducing non-contract electric arc injuries: An investigation of behavioral and organizational issues - Kathleen Kowalski-Trakofler; Edward Barrett (The National Institute for Occupational Safety and Health (NIOSH))
Problem: It is estimated that 5 to 10 arc flash explosions occur in electric equipment every day in the United States. In the mining industry the largest single injury category of electrical injuries are caused by non-contact electrical arcs. Method: This investigation progressed in two phases: (a) 836 Mine Safety and Health Administration (MSHA) reports of electric arcing incidents that occurred over a period of 11 years were reviewed, and (b) personal interviews were conducted with 32 individuals. A theoretical Safe Job Performance Model guided the study. Results: Behavioral dimensions were identified and included the effect of worker experience, judgment and decision-making ability, behavioral and organizational controls, and safety culture. Summary: The National Institute for Occupational Safety and Health (NIOSH) conducted an investigation of behavioral components associated with arc flash incidents and developed recommendations for interventions based on findings. Impact on Industry: This study fills a vacuum in electrical training with a focus on the organizational and behavioral aspects of arc flash incidents. There search is cross-cutting in its scope, in that the results apply not only to mining and construction, but many other industries employing electricians. Although the majority of mine electrical injuries are the results of burns from electrical arcs, few miners are aware that such a hazard exists. A safety training program, which includes a video and an instructor's discussion guide, was developed for electricians based on this study's findings. “Arc Flash Awareness” was released in 2007 (DHHS NIOSH PublicationNo.2007-116D) and is available through1-800 CDC-INFO. Phone:1-800232-4636 or email cdcinfo@cdc.gov. It is also available from MSHA at MSHADistribution@dol.gov or 304-256-3257 (DVD-576). Private industry is producing Portuguese and Spanish language translations.